Assessment of Upper Limb Muscle Exertion in School-Aged Children during Load Carrying - Abdalla, Faisal; Elsakori, Ahmed; Saleh, Hafed (Journal of Pure & Applied Sciences, 2025)
Carrying heavy backpacks exceeding 10% of body weight (BW) is a widespread issue among primary school students in developing countries, often linked to musculoskeletal injuries. This study proposes redistributing excess backpack loads to the arms to reduce spinal strain and evaluates the safety of this approach. An optimisation model was developed to estimate arm muscle forces in ten healthy students (age: 8.09 ± 0.85 years) during treadmill walking under three load conditions, which were 0-L (no arm load), 1-L (2.2 kg arm load), and 2-L (4.5 kg). Kinematic data were captured using a Vicon motion analysis system, and muscle forces derived from the model were compared to their maximum forces (Fmax). Results demonstrated that muscle forces increased significantly with load magnitude: biceps and triceps forces remained below safe load limits in 0-L, with 113.46 N and 115.06 N, respectively, and 1-L, with 228.34 N and 231.12 N. However, at 2-L, triceps force was 309 N,which exceeded its maximum force (Fmax = 280 N). Paired t-tests confirmed statistically significant differences between all conditions. These findings suggest that transferring 2.2 kg (1-L) from the back to the arms is biomechanically safe, whereas 4.5 kg (2-L) poses a risk of overloading arm muscles. This study provides actionable insights for optimising load distribution in schoolchildren to prevent spinal injury.